Heavy Metal Pollution Loads and Relationships of Drying Beds Sludge in Urban Wastewater Treatment Plant - Dere, Turgay (Asian Journal of Chemistry, 2013)
In this study, sludge samples were taken from Elazig city urban wastewater treatment plant drying beds in order to find seasonal heavy metal pollution load and to predict load variations in the samples. According to the results of the analysis, the acid extractable drying beds sludge heavy metal pollution loads were found as, respectively, iron, zinc, manganese, copper, chrome, nickel, lead, cobalt, cadmium. According to the correlation test applied to monthly pollution loads of the drying bed sludge, the highest positive correlations were observed between copper and cadmium (p < 0.01). After that, head sludge heavy metal pollution were found as iron-zinc, iron-nickel, iron-lead, zinc-lead, zinc-chrome, chrome-iron and nickel-zinc, respectively.